The Effective Integration of Digital Games and Learning Content - Habgood, Matthew Peter Jacob (2007)
This thesis is concerned with how the coveted user-engagement of digital games can be usefully harnessed for educational goals. Educational software has traditionally used gaming elements as a separate reward for completing learning content. The early "edutainment" sector became synonymous with this cursory "chocolate-covered broccoli" approach (Bruckman, 1999): tagging games on to learning content in order to make it more palatable. However, such methods have often proved ineffective (Kerawalla & Crook, 2005; Trushell, Burrell, & Maitland, 2001) and have been criticised for combining the worst elements of both games and education (Papert, 1998) as well as for following extrinsically motivating design models (Lepper, 1985; Parker & Lepper, 1992).